HIV Complications On Ears, Nose, Throat And Skin: Literature Review - Dinda Humayrah; Dian Amelia Abdi; Iin Fatimah Hanis (Sean Institute, 2024)
Human immunodeficiency virus (HIV) is an agent that can cause infection. HIV/AIDS can cause various complications that affect various parts of the body, including the skin, ears, nose and throat.This research is a Literature Review with a Narrative Review design. The type of data is data published from internationally accredited scientific journals.In total there are 8 studies published in the last 10 years (2012-2022) consisting of 1 prospective study, 5 cross sectional studies, and 2 case report studies. Human Immunodeficiency Virustargets CD4+ T lymphocyte helper cells, causing an extreme form of immune resistance with persistent depletion of CD4+ T lymphocyte helper cells. HIV infection that is left unchecked eventually develops into Acquired Immunodeficiency Syndrome (AIDS). At this stage, the immune system cannot prevent infection, resulting in the death of the individual due to opportunistic infections. Common ear, nose, throat and skin manifestations in HIV positive patients include oral candidiasis, enlarged lymph nodes, rhinosinusitis, allergic rhinitis, enlarged lymph nodes. clear neck, enlarged adenoids, chronic suppurative otitis media, suppurative hidradenitis, lesions on the head and neck, with the most common being rhinosinusitis. Patients with chronic HIV infection without AIDS can experience oropharyngeal candidiasis, recurrent vulvovaginal candidiasis, disseminated cutaneous herpes simplex. Skin manifestations such as seborrhoeic dermatitis, bacillary angiomatosis, varicella-zoster virus reactivation, and molluscum contagiosum infections are common and tend to be severe in HIV patients. The incidence of HIV infection continues to increase, and Indonesia is one of the Southeast Asian countries experiencing a high number of cases. In Indonesia, around 540,000 people live with HIV. The number of new HIV infections increased from approximately 21,511 in 2012 to 41,250 in 2016.